POTENSI PENGEMBANGAN TERNAK SAPI POTONG TERINTEGRASI TANAMAN KELAPA DALAM - Laode Muh Munadi (Animal Husbandry Department, Faculty of Agriculture Gorontalo State University, 2021)
The research aims to find out the potential of the development of coconut-integrated beef cattle in North Buton Regency by looking at the potential of the sub-district that became the development of beef cattle. Data collection using survey methods through sampling in designated areas has the potential of beef cattle development in plantation areas using the approach of analysis of the level of revenue and revenue of farming, analysis of the cost of cattle business, coconut business in, analysis of income of cattle and coconut farmers, and Loqation Question (LQ). The development business of coconut-integrated beef cattle business in North ButonRegency, was able to increase the income of farmers in one year, namely, Rp 5,016,778 and coconut business income of Rp 3,371,359.47.